2004
DOI: 10.1143/jjap.43.3140
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Acoustic Communication with Quadrature Amplitude Modulation in Multipath Environment

Abstract: An experiment on high-speed underwater acoustic data communication was carried out at real sea as a time-variant multipath channel. Demodulation was processed by a multichannel decision feedback equalizer (DFE) demodulator with adaptive filtering. The modulation method used was 16-quadrature amplitude modulation (16-QAM), transmitting rate was 32 k bit per second (bps), carrier frequency was 20 kHz, and bandwidth was 8 kHz (16–24 kHz). Good demodulation results were obtained at a sea trial despite the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…to cope with ISI using adaptive equalizers such as DFE [1][2][3] . Moreover, it was found that the combination of DFE and array processing can increase communication quality [4][5][6][7][8][9][10][11][12] . Although the receiver complexity significantly increases as the effect of ISI increases, the single-carrier technique achieves good communication quality even in UWA channels, and an array-processing technique can be utilized to increase communication quality with practical complexity.…”
Section: Introductionmentioning
confidence: 99%
“…to cope with ISI using adaptive equalizers such as DFE [1][2][3] . Moreover, it was found that the combination of DFE and array processing can increase communication quality [4][5][6][7][8][9][10][11][12] . Although the receiver complexity significantly increases as the effect of ISI increases, the single-carrier technique achieves good communication quality even in UWA channels, and an array-processing technique can be utilized to increase communication quality with practical complexity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) In recent years, the need for high-speed underwater acoustic communication to construct sensor networks on the sea floor or to communicate with underwater vehicles has become higher. In the Japan Agency for Marine-Earth Science and Technology (JAMSTEC), two types of research on underwater acoustic communication are in progress, one is the short range but very high speed, [3][4][5][6][7][8] and the other is low speed but very long range. For the first type of research, the development of a wideband transducer and the experiments in a water tank and at sea have been advanced.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike optical communication with the high frequency and light speed, data transfer based on sound is subject to deficiencies of low frequency and velocity, limiting the advancement of acoustic communication . Although remarkable progress has been made by introducing wavelength‐division multiplexing (WDM), time‐division multiplexing (TDM), and multilevel amplitude/phase modulation, data rate of acoustic communication is approaching its current limit, due to the fact that sound, as a scalar wave, bears no polarization or spin, as opposed to its optical counterparts. It is stringent to exploit plausible multiplexing mechanisms to encode information in a scalar field with multiple states orthogonal and compatible to existing degrees of freedom (DOF).…”
mentioning
confidence: 99%